Endoscopic ultrasound-guided drainage of a fungal liver abscess using a lumen-apposing metal stent: case report and literature review - Molinario Felice; Rimbaş Mihai; Pirozzi Giuseppe Alessandro; Rizzatti Gianenrico; Spera Gianluca; Costamagna Guido; Larghi Alberto (Sciendo, 2021)
Liver abscesses are rare entities for which percutaneous drainage is traditionally employed. The technique is simple, but associated with a significant rate of side effects and patient discomfort. We herein report a case of fungal left liver lobe abscess that was successfully treated by using EUS-guided drainage, with insertion of a large caliber lumen-apposing metal stent. The literature review we performed on the topic seems to favor, at least for abscess in the left and/or caudate liver lobes, EUS as compared to percutaneous drainage.